АЛТЫ ЖАСАР БАЛАЛАРДЫҢ ОҚЫЎ ИСКЕРЛИГИНЕ БЕЙИМЛЕСИЎ ӨЗГЕШЕЛИКЛЕРИ - Аймухаммедова, Т. (FAN va JAMIYAT, 2017)
The article deals with the features of adaptation to school of six year old children, the work’s results of pedagogical and psychological diagnostics and the effectiveness of preschool institution activity in training children to school education.